Envolvimento do receptor de potencial transitório anquirina 1 e efeito farmacológico da diosmetina na queimadura de pele induzida pela radiação UVB em camundongos - Pozza, Camila Camponogara Dalla (2021)
Excessive exposure to type B ultraviolet radiation (UVB) can lead to several changes to the skin resulting from the oxidative and inflammatory processes installed through the neuronal and non-neuronal receptors activation. Among these, vanilloid 1 (TRPV1) and ankyrin 1 (TRPA1) transient potential receptors play an essential role in the induction and modulation of skin inflammatory diseases. Studies have already demonstrated the participation of the TRPV1 channel, but not the TRPA1 channel, in the skin inflammation induced by UVB radiation. Thus, we investigated the involvement of the TRPA1 and the topical anti-inflammatory and antioxidant potential of diosmetin, a novel TRPV1 antagonist, in a model of sunburn induced by UVB radiation in mice. Ears of male Swiss mice were exposed to a single (0.5 J/cm2) or repeated (0.1 J/cm2; three exposures on alternate days) UVB radiation source. Semisolid formulations (Lanette® based cream) containing HC-030031 (TRPA1 antagonist; 0.01-1%), diosmetin (TRPV1 antagonist; 0.01-1%) or dexamethasone (positive control; 0.5%) were topically applied (immediately after UVB radiation). We evaluated inflammatory parameters (ear edema, myeloperoxidase, and N-acetyl-β-D-glycosaminidase enzymes activities, histological changes, and inflammatory cytokines levels), oxidative (quantification of reactive oxygen intermediates and superoxide dismutase and NADPH oxidase enzymes activities), and proliferative [epidermal hyperplasia (histological analysis) and nuclear cell proliferation antigen (PCNA) and TRPA1 (immunohistochemical analysis) levels]. We verified the contribution of neuronal and non-neuronal TRPA1 and TRPV1 channels on inflammatory parameters induced by UVB radiation through desensitization of cutaneous nerve endings by resiniferatoxin (RTX; 50 μg/kg s.c). In the single exposure to UVB radiation model, the topical treatment with a TRPA1 antagonist (HC-030031; 1%) or diosmetin (1%) reduced ear edema [maximum inhibition (Imax) of 70±9% and 82±9%; respectively], myeloperoxidase activity (Imax of 72±7% and 59±10%, respectively), the number of inflammatory cells infiltrated in the skin tissue (histological analysis), inflammatory cytokines levels (MIP-2 and IL-1β) and other oxidative parameters evaluated. Topical dexamethasone (0.5%) was also effective in reducing inflammatory and oxidative parameters induced by a single exposure to UVB radiation. In the repeated exposure to UVB radiation model, topical treatment with TRPA1 antagonist (0.1%) reduced ear edema, myeloperoxidase activity, and N-acetyl-β-D-glycosaminidase (Imax of 54±5%, 53±3%, and 75±7%, respectively), the number of cells infiltrated in the skin tissue, epidermal hyperplasia and levels of PCNA (Imax of 74±3%) and TRPA1 (Imax of 95±2%). Topical dexamethasone (0.5%) also reduced the inflammatory and proliferative parameters induced by repeated exposure to UVB radiation. From the denervation process by RTX, both non-neuronal TRPA1 and TRPV1 channels partially contributed to the development of ear edema induced by a single exposure to UVB radiation. At the same time, the inflammatory cell infiltration was mainly mediated by neuronal TRPA1 and TRPV1 (cutaneous nerve fibers). Thus, we propose that the TRPA1 channel induces pathophysiological states observed after exposure to UVB radiation. Our study also suggests that flavonoid diosmetin may be an effective and promising therapy for skin burns induced by UVB radiation.